The barriers, motives, perceptions, and attitudes toward research among radiology practitioners and interns in Saudi Arabia: a cross-sectional study - Alshamrani, Khalid M.; Alkenawi, Abdulkader A.; Kaifi, Reham E.; Alhulil, Khaled A.; Munshi, Wael M.; Alqurayqiri, Abdulaziz F.; Alshehri, Faisal A.; Abdulmannan, Hawazen I.; Ghulam, Enas M.; Tasslaq, Sameer E.; Aldhebaib, Ali M. (Frontiers in Medicine, 2023)
Background Research and the use of evidence-based practices are imperative to the advancement of diagnostic imaging modalities. The aim of this study was to assess the perceptions and attitudes of radiology practitioners (i.e., Technicians, Technologists or Specialists, and Senior Specialists) and interns in King Abdulaziz Medical Cities (KAMCs), Kingdom of Saudi Arabia, toward research, and to explore the various barriers and obstacles that hinder their research efforts. Methods A cross-sectional descriptive investigation was carried out from December 2022 to March 2023 among 112-KAMCs’ radiology practitioners and interns, using previously developed and validated questionnaire comprised of five distinct sections, each serving a specific purpose, and with a non-probability convenient sampling technique. Descriptive statistics were generated for participants’ demographics, and chi-square and fisher’s exact tests were used to examine the association between participants’ demographics and their involvement in research. Results Among the 137 KAMCs’ radiology practitioners and interns who were invited to participate, 112 responded and completed the questionnaire, resulting in an overall response rate of 81.75%. Radiology practitioners and interns from various medical imaging subspecialties were found to be involved in research to the extent of 83%, with nearly half (40.9%) of them have had publications, and 53.3% of these publications being either cross-sectional studies or retrospective clinical studies. A lack of time (66.1%), a lack of a professional supervisor support program (50.9%), and deficiency in research skills (45.5%) were common obstacles that may impede the participants’ ability to conduct research. The most common motives for participants to conduct research were the desire to improve their resumes (69.6%), get accepted into postgraduate radiology programs (58%), and improve their research skills (52.7%). Conclusion KAMCs’ radiology practitioners and interns have a positive attitude toward performing research. Despite the high percentage (83%) of those involved in research, the number of publications remains low. A crucial step to advancing the profession’s evidence base is engaging radiology practitioners and interns in research and encouraging radiology practitioner-led research. The study findings can serve as a valuable basis for designing developmental programs aimed at overcoming research obstacles among healthcare professionals in Saudi Arabia.